Street artը՝ որպես պատմութեան կրող. Հայաստանի օրինակը - Խառատեան, Մանէ (տպ. Atlas)
From the moment of the formation of street art till today, the form is still going through a certain development process. It performs the same function as all forms of classical and contemporary art: it reproduces reality and interprets it in its own way, though the terminology is still undergoing changes. Everywhere street art has been formed under conditions of historical change and is directly influenced by that change. This applies to both the whole world and Armenia. The active regions of street art in Armenia are Yerevan and Gyumri. Today we can record current processes, which after some time will help to analyse and understand the whole process in retrospect.
Keywords: Արուեստ